Diagnosis and Treatment of NMO Spectrum Disorder and MOG-Encephalomyelitis - Borisow, Nadja; Mori, Masahiro; Kuwabara, Satoshi; Scheel, Michael; Paul, Friedemann (Frontiers in Neurology, 2018)
Neuromyelitis optica spectrum disorders (NMOSD) are autoantibody mediated chronic inflammatory diseases. Serum aAntibodies (Abs) against the aquaporin-4 water channel lead to recurrent attacks of optic neuritis, myelitis and/or brainstem syndromes. In some patients with symptoms of NMOSD, no AQP4-Abs but Abs against myelin-oligodendrocyte-glycoprotein (MOG) are detectable. These clinical syndromes are now frequently referred to as “MOG-encephalomyelitis” (MOG-EM). Here we give an overview on current recommendations concerning diagnosis of NMOSD and MOG-EM. These include antibody and further laboratory testing, MR imaging and optical coherence tomography. We discuss therapeutic options of acute attacks as well as longterm immunosuppressive treatment, including azathioprine, rituximab and immunoglobulins.